Women in politics and bureaucracy - Huq, Jahanara; Women for Women (Organization : Bangladesh) (Dhaka : Women for Women, 1995)
With reference to Bangladesh; contributed articles.
Includes bibliographical references.
Keywords: Women Politicians -- Bangladesh; Bangladesh -- Politics and government